Pelatihan Pemanfaatan Media Pembelajaran Berbasis Kebutuhan Siswa bagi Guru TPA Babussalam Bogor - Fauzy Rahman Kosasih; Juhana Juhana; Suratinah Suratinah (Universitas Mathla'ul Anwar Banten, 2021)
A TRAINING OF THE UTILIZATION OF STUDENT NEED-BASED LEARNING MEDIA FOR BABUSSALAM AL-QUR'AN EDUCATION KINDERGARTEN (AEK) BOGOR TEACHERS. This community service program entitled